Short-Term Gains, Long-Term Loss: Investigating EFL Students’ Retention of Academic Articles After Guided Writing - Jaya, Sinarman (Institut Agama Islam Negeri Madura, 2025)
Guided academic writing courses have become common in EFL higher education, often helping students produce publishable articles. However, whether such instruction leads to lasting understanding or merely short-term task completion remains unclear. This study investigated how well undergraduate EFL students retained the content of their self-written academic articles after completing a one-semester guided writing course. Using an explanatory sequential mixed methods design, the research involved 40 students who completed a final exam task requiring them to reconstruct the abstract and main argument of their article without referring to the original. Their performance was then followed by semi-structured interviews with a stratified sample, supported by semester-long observational field notes. Results indicated that over 85% of students were unable to recall the core ideas from their own articles accurately. Thematic analysis, interpreted through the lenses of constructivist learning theory, levels of processing, and authorial identity, revealed several contributing factors: shallow cognitive engagement, limited topic relevance, over-reliance on templates and AI tools, and a lack of personal ownership in the writing process. These findings highlight a disconnection between writing performance and long-term learning. Unlike prior studies focusing primarily on writing quality or output, this research addressed post-writing memory, a dimension rarely explored in EFL writing research. The study calls for a pedagogical shift toward more reflective, cognitively engaging, and identity-driven writing practices that promote meaningful retention and deeper academic development.